Linking Presentation to Pathology: A Prospective Study of Patient Complaints, Risk Profiles, and Histopathological Results in Bladder Cancer in Derna City - Abdulsalam Ahmeedah Abdulsalam (المجلة الأفروآسيوية للبحث العلمي, 2025)
Bladder cancer shows considerable geographical variation in presentation and risk factors, yet prospective data from North Africa remain limited. This study prospectively characterized the clinical presentations, risk profiles, and histopathological features of bladder cancer patients in Eastern Libya. A prospective observational study was conducted involving 91 newly diagnosed patients at Al-Wahda Hospital, Derna, from January to December 2024. Data on demographics, clinical presentation, risk factors, imaging findings, and histopathology were collected and analyzed using SPSS version 26.0. The cohort demonstrated a male predominance (80.2%) with a mean age of 66.4 ± 8.7 years. Hematuria was the most common presenting symptom (93.4%), while 6.6% were asymptomatic. Smoking prevalence was high (84.6%), and 33% reported occupational exposures. Histopathological analysis showed that 94.5% of cases were urothelial carcinoma, followed by squamous cell carcinoma (3.3%) and adenocarcinoma (2.2%). Most tumors were low-grade (90.1%) and non-muscle-invasive (95.6%). CT program demonstrated higher sensitivity (96.7%) compared with ultrasound (90.1%). Significant predictors of high-grade disease included age >70 years (OR = 2.32, p = 0.031), smoking >40 pack-years (OR = 2.89, p = 0.007), and lymphovascular invasion (OR = 10.89, p < 0.001). This study provides the first comprehensive characterization of bladder cancer in Eastern Libya, highlighting distinct epidemiological patterns and underscoring the need for region-specific prevention and diagnostic strategies.